THE CENTER FOR ISLAMIC CIVILIZATION IN UZBEKISTAN: AN INTERDISCIPLINARY APPROACH TO THE STUDY OF CULTURAL HERITAGE (The Journal of Interdisciplinary Human Studies, 2026)
This article discusses the recently established Center for Islamic Civilization in Uzbekistan. It seeks to depict the Center as a mirror of Central Asian heritage in science and the arts, as well as its rich cultural dimension. The article clarifies the role and importance of the Center for Uzbekistan and its people as a major cultural site and a driver of economic and intellectual development.
Keywords: Center for Islamic Civilization, Islamic Renaissance, scholars, Uzbekistan, Third Renaissance.